Managing Job Stress to Boost Employee Performance: A Case Study at Rumah Sakit X - Zulfikar Muhammad Hasan; Kanina Sista; Hery Sutanto; Primadia Putri Harmastuti; Nurendah Shinta Rachmawati (Journal of International Conference Proceedings, 2024)
This study examines the relationship between job stress, job satisfaction, and employee performance, focusing on the mediating role of job satisfaction. The research was conducted at Rumah Sakit X with 118 respondents, comprising non-medical staff, who completed a structured questionnaire. The findings reveal a strong negative correlation between job stress and employee performance, indicating that higher levels of stress are associated with lower employee productivity and effectiveness. Additionally, job stress was found to have a significant indirect negative impact on employee performance when mediated by job satisfaction. This suggests that job stress not only directly hampers performance but also reduces job satisfaction, which in turn further diminishes employee performance. The study underscores the importance of managing workplace stress to foster better job satisfaction and improve overall performance. These findings emphasize the need for organizations to implement stress management strategies and create supportive environments that promote employee well-being. By addressing the root causes of job stress and enhancing job satisfaction, organizations can mitigate its adverse effects on performance, ensuring a more productive and engaged workforce. The results contribute to the growing body of research linking workplace stress, satisfaction, and performance, providing actionable insights for organizational improvement.